2017
DOI: 10.1515/raft-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Shielding Efficiency of a Fabric Based on Amorphous Glass-Covered Magnetic Microwires to Radiation Emitted by a Mobile Phone in 2G and 3G Communication Technologies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Comparing present results to the older ones referring to SAR values decrease due to using the fabric to cover the mobile phone (Miclaus, et al, 2017), one can address only one frequency -of 1.95 GHz. Present measurements show that only the H-field component is shielded by the fabric, and that shielding efficiency of H-field level at this frequency is in the range (14-17) dB.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Comparing present results to the older ones referring to SAR values decrease due to using the fabric to cover the mobile phone (Miclaus, et al, 2017), one can address only one frequency -of 1.95 GHz. Present measurements show that only the H-field component is shielded by the fabric, and that shielding efficiency of H-field level at this frequency is in the range (14-17) dB.…”
Section: Resultsmentioning
confidence: 51%
“…Present experimental approach aimed to characterize a sheet of amorphous fabric for its electromagnetic shielding properties, by first analyzing its composition and internal geometry by means of electronic microscopy and then by preliminary testing the shielding efficiency, separately for the electric (E) and for the magnetic (H) field components of an electromagnetic wave travelling through it. The motivation of present study is based on some previous findings of ours (Miclaus, et al, 2017) which showed that this fabric used to cover a mobile phone which emitted at 0.89 MHz and at 1.95 GHz, greatly diminished (with 70-76%) the specific absorption rate (SAR) of electromagnetic energy deposited inside a phantom head wearing the covered terminal at the ear. Therefore we considered important to investigate this time a larger frequency range, (1-3) GHz, and in conditions of far-field irradiation (but applying a non-standardized protocol) and to identify which component of the wave is shielded more, E or H. In the case of previous SAR measurements, the probe used in the standardized protocol was an E-field one, which was immersed in the liquid filling the phantom head exposed to radiation from the mobile phone, and the measurement took place in the near field of the emitting antenna.…”
Section: Introductionmentioning
confidence: 99%
“…A number of standardized techniques and procedures are presently used to quantify the SE of materials, either in near field or in far field conditions of shield positioning nearby the emitting antenna [35][36][37][38][39][40]. Non-standard methods of measurement are also used mainly when comparisons with well-characterized materials is available or for some specific needs of the shield [41][42][43][44][45]. In this paper, a non-standardized procedure was applied for the SE measurement using near field probes [46].…”
Section: Materials Measurement System and Proceduresmentioning
confidence: 99%
“…presents a synthesis of the results for Bekinox knitted structures. Regarding the CEM standards, manufacturers have used both national and international standards[9][10][11][12].…”
mentioning
confidence: 99%